2020
DOI: 10.1002/aoc.5841
|View full text |Cite
|
Sign up to set email alerts
|

Naked‐eye detection of Cu (II) and Fe (III) based on a Schiff Base Ruthenium complex with nicotinohydrazide

Abstract: A cyclometalated ruthenium (II) complex 1 [(Ru (Phen)2(Pbznh)]+ PF6− (Phen = 1,10‐phenanthroline and Pbznh = N‐(4‐(pyridine‐2‐yl)benzylidene) nicotinohydrazide) with nicotinohydrazide as a functional group was synthesized and characterized. Changes of its absorption spectra and color induced by Cu2+ and Fe3+ were systematic investigated. The results demonstrated that complex 1 could be served as a colorimetric probe to fast, selective and sensitive detection of Cu2+ and Fe3+ both in acetonitrile and filter pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 60 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…3B) also showed that the emission intensities of Ru1 and Ru2 decreased with an increase of Fe 2+ concentration, which means that Ru1 and Ru2 can chelate Fe 2+ . The binding assays using Job's method 50 showed that Ru1 or Ru2 formed a 1 : 1 complex with Fe 2+ (Fig. S8 †).…”
Section: Inhibition Of Jmjd Activity By Ru1 and Ru2mentioning
confidence: 99%
“…3B) also showed that the emission intensities of Ru1 and Ru2 decreased with an increase of Fe 2+ concentration, which means that Ru1 and Ru2 can chelate Fe 2+ . The binding assays using Job's method 50 showed that Ru1 or Ru2 formed a 1 : 1 complex with Fe 2+ (Fig. S8 †).…”
Section: Inhibition Of Jmjd Activity By Ru1 and Ru2mentioning
confidence: 99%
“…[19] Therefore, to avoid a serious impact on human beings, the determination of these heavy metal ions is a very attractive research topic. Generally, interactions between probes and these metal ions mostly are based on coordinative interactions, [15,16,[20][21][22][23][24][25] or thus induced chemical reactions. [17,[26][27][28][29] According to the strong affinity of Hg 2+ with S atom, [30,31] we have synthesized several cycloruthenated 2-thienyl complexes that have been used to detect Hg 2+ with high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%